The Use of Gold Dinar and Silver Dirham in Moslem Countries in the Contemporary Era - Ichsan, Muchammad (Jurnal Media Hukum, 2017)
The dominance of the US dollar and other developed countries currencies, as well as the fact that their currencies have fallen behind, have urged groups of Moslems in some countries to call for the use of gold dinar and silver dirham as a medium of exchange. This paper aims at examining the need, application, and law on the use of gold dinar and silver dirham from the Islamic perspective. To reach the goal set at this moment, a descriptive method is employed in the writing while an analytical method is used to scrutinize the relevant problems. This study finds that in the current situation Moslems need to use gold dinar and silver dirham for their financial contracts. The use of gold dinar and silver dirham is applicable in this modern era although there are some obstacles and problems. Lastly, the use of gold dinar and silver dirham as a medium of exchange is allowed from the Islamic perspective based on some propositions.